DEMOGRAPHIC CHANGES IN THE REPUBLIC OF UZBEKISTAN AND ITS IMPACT ON THE ECONOMY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article examines and analyzes key demographic trends such as opulation growth, changes in age structure, urbanization and migration. Particular attention is paid to their impact on the labor market, consumption levels, social sphere and economic growth. Possible risks and prospects that demographic processes create for the sustainable development of Uzbekistan are identified.